CONTROLS BY SATURATION STATE ON ETCH PIT FORMATION DURING CALCITE DISSOLUTION - Teng H.H. (My University, 2004)
Dissolution experiments were conducted on {1014} cleavage faces of calcite at various under-saturations to determine how the saturation state controls etch pit formation. Experimental observations were made by using in situ fluid cell Atomic Force Microscopy. Three dissolution modes were observed. When the saturation index Ω > 0.541, no etch pit formation was seen and dissolution primarily occurred at existing steps. When Ω decreased to Ωc = 0.541-0.410, the first visible pits appeared and continuous reduction in saturation state slowly increased the pit density on terraces while dissolution simultaneously proceeded at step edges. Finally, when the saturation state fell below Ωmax = ~0.007, a precipitous increase in pit density took place that sharply contrasted to the ordered fashion of pit formation observed at saturation conditions above this level. These observations are interpreted to be two-dimensional and unassisted pit formation at Ω < ~0.007, defect- and step-assisted dissolution in between Ω = 0.541 and 0.007, and existing step-induced dissolution for Ω > 0.541.The values of Ωc are in good agreement with the dislocation theory's predicted critical under-saturations for pit formation at line dislocations. The occurrence of Ωmax is not directly predicted but is a logical consequence of dissolution thermodynamics. These findings suggest that (1) dissolution near and far from equilibrium (i.e., Ω > Ωc, Ω < Ωmax) is not controlled by dislocations, therefore (2) dislocation density should significantly impact dissolution rate only in the saturation range of Ωmax < Ω < Ωc; (3) dissolution kinetics and chemical affinity of dissolution reactions should have a non-linear relationship: at sufficiently close to equilibrium, when dislocations cannot open up to form etch pits, the dissolution kinetics will be limited by the number of existing steps; at far from equilibrium, when pits are able to form in defect-free regions, the dissolution rate will be capped by the maximum number of achievable steps.These findings may provide explanations for several well-observed geochemical relationships, including the weak dependence of dissolution rate upon dislocation density in distilled water and the 'plateau' behavior of dissolution kinetics both near and far from equilibrium. The explosive occurrence of unassisted pit nucleation at Ω ~ Ωmax is not predicted by the current dissolution rate equations. This suggests that an accurate 'general' rate law describing universal dissolution processes has yet to be developed.